Contagious Sapiosexuality: Dreaming Conference Seduction as Ethics of Qualitative Research - Wolgemuth, Jennifer R.; Marn, Travis M. (Reconceptualizing Educational Research Methodology, 2022)
In this paper we engage Baudrillard’s (1979/1990) writings on seduction to ‘dream up’ seduction as an ethical and generative-destructive force of qualitative research. Beginning with a dreamy conference seduction, we argue that seduction keeps us qualitative researchers thinking, moving, risking, and being passionate about our work and each other. As a playful, sometimes frivolous, yet deeply terrifying process, seduction moves us beyond ourselves and into theoretical unknowns; enables us to risk ourselves in ethically listening to others’ truths. We show and argue that conferences can be ripe spaces for the spread of contagious sapiosexuality and urge qualitative researchers to experiment and play with conference seductions.